Evaluación de los métodos de extracción de compuestos fenólicos (antocianinas) a partir del fruto del corozo (Bactris Guineensis) (2021)
In this research work we seek to define the best alternative for obtaining anthocyanins from the corozo fruit (Bactris guineensis) through the bibliographic collection of different authors where they address the extraction of phenolic compounds and in turn the separation of anthocyanins.